2022
DOI: 10.3390/s22031087
|View full text |Cite
|
Sign up to set email alerts
|

Compact Sphere-Shaped Airflow Vector Sensor Based on MEMS Differential Pressure Sensors

Abstract: This paper presents an airflow vector sensor for drones. Drones are expected to play a role in various industrial fields. However, the further improvement of flight stability is a significant issue. In particular, compact drones are more affected by wind during flight. Thus, it is desirable to detect air current directly by an airflow sensor and feedback to the control. In the case of a drone in flight, the sensor should detect wind velocity and direction, particularly in the horizontal direction, for a sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The root mean square errors of the wind speed and direction, which corresponded to the accuracies, were 0.24 m/s and 3.62°, respectively. It was confirmed that they were substantially improved, because the previous study's fifth order polynomial regression results using the same training/test data set indicate root mean square errors of 0.55 m/s and 6.29° [29]. Although the wind direction intervals and learning methods differed, the root mean square errors for wind speed and direction improved by 56.4% and 42.4%, respectively, in the same order of magnitude as in the simulation.…”
Section: B Learning Using the Sensor Outputssupporting
confidence: 70%
See 3 more Smart Citations
“…The root mean square errors of the wind speed and direction, which corresponded to the accuracies, were 0.24 m/s and 3.62°, respectively. It was confirmed that they were substantially improved, because the previous study's fifth order polynomial regression results using the same training/test data set indicate root mean square errors of 0.55 m/s and 6.29° [29]. Although the wind direction intervals and learning methods differed, the root mean square errors for wind speed and direction improved by 56.4% and 42.4%, respectively, in the same order of magnitude as in the simulation.…”
Section: B Learning Using the Sensor Outputssupporting
confidence: 70%
“…The measurements in specific direction regions significantly deteriorate because of this phenomenon [28]. That effects were observed with the compact airflow sensor previously fabricated by our group [29]. Therefore, there is potential for further improvement with regard to the wind direction accuracy.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The cantilever fabrication process is illustrated in Figure 4C; details are given in a previous study. 21 The cantilever with resistance of the kΩ order was designed to sensitively respond to deformation under pressure of the order of several Pa. 28,29 The thickness of device Si layer, SiO2 layer, and handle Si layer in the SOI wafer was 0.15 , 1.0 , and 300 μm, respectively. First, a piezo layer was formed on the device Si layer.…”
Section: Piezoresistive Cantilevermentioning
confidence: 99%